Root cause study on an uncommon coating adhesion failure of hot-dip galvanized boron added low carbon steel. (August 2022) - Jin, Xinyan; Peng, Jun; Qian, Hongwei
Highlights: Boron enrichment at the coating/steel interface prevented the formation of Fe-Al inhibition layer. Vaporization of external boron oxidation polluted the rollers and the furnace inner walls. Dew point increasing improved the coating adhesion of boron added low carbon steel. Abstract: In this study, the root cause of an uncommon coating adhesion failure of hot-dip galvanized boron added low carbon steel was investigated. Metallurgical characterizations were performed by GDOES, SEM, AES, FIB and EDS. It was found that the coating adhesion failure was caused by the enrichment of boron at the coating/steel interface, which significantly prevented the formation of Fe-Al inhibition layer. The root cause of boron enrichment was further attributed to the external oxidation of boron during the annealing process. The vaporization of B2 O3 and the formation of BN in the annealing furnace polluted the rollers and the inner furnace walls, which caused further boron contamination on the following steel surface. The suppression of boron external oxidation by dew point increasing effectively improved the coating adhesion of hot-dip galvanized boron added steel.